Cerebral glycolysis: a century of persistent misunderstanding and misconception - Schurr, Avital (Frontiers in Neuroscience, 2014)
Since its discovery in 1780, lactate (lactic acid) has being blamed for almost any illness outcome in which its levels were elevated. Beginning in the mid 1980s, studies, both on muscle and brain tissues, have suggested that lactate plays a role in bioenergetics. However, great skepticism and, at times outright antagonism was exhibited by many to any perceived role of this monocarboxylate in energy metabolism. The present review attempts to trace the negative attitudes about lactate to the first four or five decades of research on carbohydrate metabolism and its dogma by which lactate is a useless anaerobic end-product of glycolysis. The main thrust here is the review of dozens of scientific publications, many by the leading scientists of their times, through the first half of the 20th century. Consequently, it is concluded that there exists a barrier, described by Howard Margolis as “habit of mind,” that many scientists find impossible to cross. The term suggests “entrenched responses that ordinarily occur without conscious attention and that, even if noticed, are hard to change.” Habit of mind has undoubtedly played a major role in the above mentioned negative attitudes toward this lactate. As early as the 1920s, scientists investigating brain carbohydrate metabolism had discovered that lactate can be oxidized by brain tissue preparations, yet their own habit of mind redirected them to believe that such an oxidation is simply a disposal mechanism of this “poisonous” compound. The last section of the review invites the reader to consider a postulated alternative glycolytic pathway in cerebral and, possibly, in most other tissues, where no distinction is being made between aerobic and anaerobic glycolysis; lactate is always the glycolytic end product. Aerobically, lactate is readily shuttled and transported into the mitochondrion, is converted to pyruvate via a mitochondrial lactate dehydrogenase (mLDH) and then entered the tricarboxylic acid (TCA) cycle.